TINJAUAN SYARIAH TENTANG PEGADAIAN SYARIAH (RAHN) - Subagiyo, Rokhmat (An-Nisbah: Jurnal Ekonomi Syariah, 2014)
People in this country are so familiar with the word pawnshop, especially, people who are not bankable or diffculties in accessing bank loans or fnancing. When someone  needs  urgent funds quickly ,while he does not have the cash or savings fund, so, the third party funding becomes altervative solution. The population of Indonesia, according to the census consist 250 million people, will provide great opportunities for pawnshops. An increasing number of customers, profts, and outlets  occur not only in  conventional pawnshops, but also  in Shariah pawnshops. Grounding in the operation of pawn Sharia is Dewan Syariah Nasional MUI number: 25/DSN-MUI/III/2002 dated June 26, 2002 on Rahn, fatwa number: 26/DSN-MUI/ III/2002 of gold and Rahn: 68/DSN-MUI/III/2008 on tasjily rahn. Assessment in muamalah, should be known as Rahn and contract provisions in general, in order to achieve syar’I ful transaction and legimate and lawful proft  So blessing God will be obtained and felt by all, without any hesitancy in running practice pawnshop.Keywords : Pawn Shari’ah , Rahn and contract